2009
DOI: 10.1126/science.1170867
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Action: Public Opinion and the Occurrence of International Terrorism

Abstract: The predictors of terrorism are unclear. This paper examines the effect of public opinion in one country toward another country on the number of terrorist attacks perpetrated by people or groups from the former country against targets in the latter country. Public opinion was measured by the percentage of people in Middle Eastern and North African countries who disapprove of the leadership of nine world powers. Count models for 143 pairs of countries were used to estimate the effect of public opinion on terror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 11 publications
3
50
0
1
Order By: Relevance
“…These topics are basic in modern society because terrorism is growing both in rich and developing nations (Newman, 2006;Reardon, 2015). Many studies endeavour to clarify the direct and indirect determinants of terrorism (Abadie, 2005;Crenshaw, 1981;Newman, 2006;Freytag et al, 2011;McAllister and Schmid, 2011), though predictors of terrorism are often unclear factors in different societies (Krueger and Malečková, 2009). Some sources of terrorism are economic factors (Blomberg et al, 2004;Krueger and Malečková, 2003), political factors (Coggins, 2015), social factors (Krueger and Malečková, 2003), etc.…”
Section: Overview Of the Problemmentioning
confidence: 99%
“…These topics are basic in modern society because terrorism is growing both in rich and developing nations (Newman, 2006;Reardon, 2015). Many studies endeavour to clarify the direct and indirect determinants of terrorism (Abadie, 2005;Crenshaw, 1981;Newman, 2006;Freytag et al, 2011;McAllister and Schmid, 2011), though predictors of terrorism are often unclear factors in different societies (Krueger and Malečková, 2009). Some sources of terrorism are economic factors (Blomberg et al, 2004;Krueger and Malečková, 2003), political factors (Coggins, 2015), social factors (Krueger and Malečková, 2003), etc.…”
Section: Overview Of the Problemmentioning
confidence: 99%
“…We created the units of observation by making pairs of countries (n_pairs = Y X ⋅ ) (Krueger and Malečková 2009). Not all countries X were asked about countries Y; in total, we created 121 pairs.…”
Section: Datamentioning
confidence: 99%
“…The dependant variable takes values from 0 to 23 15 and the value zero represents almost 73% of the total 120 observations, therefore, we tested whether the zero-inflated negative binomial model provides a fit (Krueger and Malečková 2009). We performed the Vuong test and found that negative binomial model is favored at the 10% significance level.…”
Section: Statisticsmentioning
confidence: 99%
See 2 more Smart Citations